2018
DOI: 10.5937/zrpfns52-18855
|View full text |Cite
|
Sign up to set email alerts
|

The role of public policy reservation in international contracts

Abstract: Бо ја на Д. Ри стић, са рад ник у на ста ви Уни вер зи тет у Но вом Са ду Прав ни фа кул тет у Но вом Са ду B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…According to the same authors it varies from 0.65 to 1.11 fawns per one fully mature female, depending on the hunting area. In Vojvodina, according to the research by Ristić (1999), the real growth of roe deer varies from 0.45 to 0.90, on average 0.63. Popović et al (2007), in addition to losses, also showed the way of managing the experimental areas in real terms.…”
Section: Resultsmentioning
confidence: 99%
“…According to the same authors it varies from 0.65 to 1.11 fawns per one fully mature female, depending on the hunting area. In Vojvodina, according to the research by Ristić (1999), the real growth of roe deer varies from 0.45 to 0.90, on average 0.63. Popović et al (2007), in addition to losses, also showed the way of managing the experimental areas in real terms.…”
Section: Resultsmentioning
confidence: 99%
“…According to the research of Ristic (2005), around 5.4 million pheasants were released in the hunting grounds in Vojvodina, mostly aged 5-6 and 7-8 weeks. For the period from 1973 to 2000, the percentage of catch ranged from the minimum recorded in 2000 (10.54%) to a maximum of 28.77% in 1973.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1: Market prices in euros for 2021/22 The shooting structure roebucks and does accounted for 41.33% and in fawns for 17.33%. On the basis of a previous research an average trophy value shown in Table 2 was calculated on the basis of the nine hunting grounds in the territory of Serbia (Barajevska river, Jadar, Takovo, Dubrava, Klisura, Kamenica, Majsinjske mountains, Resava, Krilaš) where 1,184 roe deer trophies were evaluated (Popović et al, 2023) according to the formula of the International Council for Game and Wildlife Conservation CIC (Beuković and Popović, 2014;Ristić and Tiodorović, 2009;Trense et al, 1981;Frković, 1989). An average body mass of roebucks was 20.08 kg (Popović et al, 2017) while of does and fawns it was 17.25 kg and 12.60 kg -respectively (Popović, 1998;Popović et al, 2003).…”
Section: Methodsmentioning
confidence: 99%